Professional identity of nurses in pandemic times: new/old challenges reproduced in news media - Loiza Broering; Maria Itayra Coelho de Souza Padilha; Elaine Cristina Novatzki Forte; Maria Angélica de Almeida Peres (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze aspects related to the professional identity of nurses during the COVID-19 pandemic usingnews media as a source. Method: Qualitative, and retrospective document study with 51 reports from Folha de São Paulo from March to December 2020. Data was organized using ATLAS.ti, with Thematic Content Analysis and discussion from the theoretical perspective of Claude Dubar. Results: Three categories were formed: Identity captured by the images reflected on the text; The identity symbolized by the support of nurses to those who need care; and The identity symbolized by the support of nurses to those who need care. Conclusion: Despite the fact that the image of nurses is still mistakenly apprehended, the way they provide care, their commitment to the population, and their scientific mindedness ensured visibility and enabled a more empowered and secure identity for their role in society.